Evidence of genetic monogamy in the lemur Indri (Indri indri). Issue 6 (10th June 2019) - Bonadonna, Giovanna; Torti, Valeria; De Gregorio, Chiara; Valente, Daria; Randrianarison, Rose Marie; Pozzi, Luca; Gamba, Marco; Giacoma, Cristina
Abstract: Monogamy is a rare strategy among mammals but relatively common among primates. The study of the evolution of monogamy in mammals and primates is lacking empirical studies that assess the relationship between a pair‐living social organization and genetic monogamy. Sexual or genetic monogamy can only be assessed by performing molecular analyses and investigating rates of extra‐pair paternity (EPP). Studying the occurrence of EPP can provide valuable insights into reproductive strategies and their adaptive value. The indri is a pair‐living primate that lives in stable groups. Their social units are composed of the reproductive pair and up to four more individuals, but extra‐pair copulation (EPC) can occur. This raises the question of whether this event may or may not lead to EPP. Here, we investigated whether a pair‐living social organization corresponds to genetic monogamy in indris ( Indri indri ). We analyzed the paternity of 12 offspring from seven pairs using a set of six microsatellite loci on fecal samples (mean number of alleles 11.7 ± 1.8 (mean ± standard deviation). We found that in 92% of cases the genetic profile of the offspring matched the paired male of the group for all the loci considered. In the only case of paternity mismatch, the paternity assignment remained inconclusive. Our results show that I. indri genetic monogamy is the norm and supports the hypothesis that pair‐living social organization is associated with low EPP rate. Also, our results are in contrast with the hypothesis of infertility as a reason to engage in EPC for this species. Abstract : Spatial distribution of the indri groups included in the genetic and paternity analyses (solid green polygons), and the schematic representation of unsampled neighboring groups (gray striped polygons, GX1 to GX7). The uppercase names within each studied group are the social fathers; the lowercase names are the offspring tested. "*" denotes the only individual we found with inconclusive paternity assignment. HIGHLIGHTS: In 92% of cases, the paired male of the group did not have any locus mismatch with the offspring. In the only case of paternity mismatch, we were not able to assign the sire identity. Our finding suggests that genetic monogamy is the norm in the indri, although EPC can occasionally occur.